Significados asignados por madres venezolanas inmigrantes a su proyecto de vida y relaciones parentales (2019)
The economic, political and social crisis of Venezuela has lead to the masive migration of inmigrates mothers to the nacional teritory, whose situation, condition and position are vulnerable for dificulties. This situation brings up the questions: what is the life project in Colomiba after leaving their country?, likewise, what is the parental relationship and the way to raise their children?, in relation with theses questions an analysis is made of the answers, moreover, the description and construction of its meanings. The theoritical basis is focused on life Project by D’Angelo (1997) and parental styles by Baumrind (1967 y 1971).